Diabetes and the risk of non-Hodgkin’s lymphoma and multiple myeloma in the European Prospective Investigation into Cancer and Nutrition - Aneire E. Khan; Valentina Gallo; Jakob Linseisen; Rudolf Kaaks; Sabine Rohrmann; Ole Raaschou-Nielsen; Anne Tjønneland; Hans E. Johnsen; Kim Overvad; Manuela M. Bergmann; Heiner Boeing; Vasiliki Benetou; et al. (Haematologica, 2008)
Background Non-Hodgkin’s lymphomas are a heterogeneous group of neoplasms arising from the lymphopoietic system including a wide range of subtypes of either B-cell or T-cell lymphomas. The few established risk factors for the development of these neoplasms include viral infections and immunological abnormalities, but their etiology remains largely unknown. Evidence suggests that certain medical conditions may be linked, through immunosuppression, to the risk of non-Hodgkin’s lymphoma. Multiple myeloma is a neoplasm of plasma cells that accounts for approximately 15% of lymphopoietic cancers. Increases in the incidence of non-Hodgkin’s lymphoma and multiple myeloma in the past implicate environmental factors as potential causal agents.Design and Methods In the European Prospective Investigation into Cancer and Nutrition (EPIC), 1,213 histologically confirmed incident cases of non-Hodgkin’s lymphoma and multiple myeloma (594 men; 619 women) were identified during a follow-up of 8.5 years. Cox proportional hazard models were used to explore the association between self-reported diabetes, diagnosed after 30 years of age, and the risk of non-Hodgkin’s lymphoma overall and multiple myeloma and various lymphoma subtypes.Results We found no association between a personal history of diabetes and the risk of non-Hodgkin’s lymphoma overall in men (HR: 1.28, 95% CI: 0.89–1.84), in women (HR: 0.71, 95% CI: 0.41– 1.24), or in men and women combined (HR: 1.09, 95% CI: 0.80–1.47). Among the B-non-Hodgkin’s lymphoma subtypes, we observed a statistically significant increased risk of B-cell chronic lymphocytic leukemia (HR: 2.0, 95% CI: 1.04–3.86) in men, but not in women (HR: 1.07, 95% CI: 0.33–3.43).Conclusions This prospective study did not provide evidence for a role of self-reported diabetes in the etiology of non-Hodgkin’s lymphoma overall or multiple myeloma. We found an increased risk of B-cell chronic lymphocytic leukemia among men with diabetes, but not among women. We hypothesize that diabetes may not play a causal role in the etiology of B-cell chronic lymphocytic leukemia, though the underlying pathogenic mechanisms of both disorders may include shared genetic, host and/or environmental susceptibility factors.